Problematika Kedudukan Ahli Waris Pengganti dalam Hukum Islam - Sri Banun; Muhammad Azmi (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The family is the smallest unit in society, within which rights and obligations exist as in social life in general. In fulfilling individual needs and interests, conflicts often arise, including disputes over inheritance distribution. Inheritance refers to the property left behind by a deceased person, which must be distributed to entitled heirs in accordance with Islamic law or customary law applicable within the community. Problems frequently emerge regarding the position of substitute heirs, particularly nephews, within the Islamic inheritance system. This study entitled “Various Aspects of Family Law in Indonesia: The Problematics of the Position of Nephews as Substitute Heirs in Islamic Law” aims to examine the status of substitute heirs in inheritance distribution and to identify the conditions under which substitute heirs are recognized in Islamic law. The research employs a normative method with a library-based approach, analyzing classical fiqh literature and scholarly opinions. The data consist of primary and secondary sources collected through document study. The findings indicate that a substitute heir is recognized when the primary heir dies after the testator but before the inheritance has been distributed, allowing the substitute heir to receive the share in accordance with Islamic legal provisions.